Evaluation of Skin Prick-Test Reactions for Allergic Sensitization in Dogs With Clinical Symptoms Compatible With Atopic Dermatitis. A Pilot Study - Carmona-Gil, Ana M.; Sánchez, Jorge; Maldonado-Estrada, Juan (Frontiers in Veterinary Science, 2019)
Skin prick-test is the first choice for the detection of type I hypersensitivity in human atopic dermatitis. Canine atopic dermatitis resembles several symptoms of the disease in the human counterpart. In canine atopic dermatitis, intradermal testing is the test of choice, and there are few reports on the use of skin prick test in dogs. The purpose of this study was to evaluate skin prick test reactions in atopic dogs and a healthy control group to 11 environmental allergens. Eleven glycerinated allergens were applied on the left lateral thorax of nine atopic dogs and nine healthy dogs. The skin was pricked with a feather lancet and evaluated for the positive percutaneous reaction at 5, 10, 15, and 20 minutes after the application of the allergens. Data were analyzed by the Shapiro-Wilk test to test for normal distribution. Data that did not meet normality were analyzed by a one-sided Wilcoxon ranked sum test with a p-value of 0.05. Six out of 9 atopic dogs tested positive for at least one of the allergens tested. None of the dogs in the control group showed a positive reaction to the allergens included in the test. Blomia tropicalis, Dermatophagoides farine, and Dermatophagoides pteronyssinus exhibited the highest reaction rate among the group of atopic dogs. There was not a statistical difference in the histamine reaction (positive control) between both groups. In this set of dogs, the test exhibited a 100% specificity and a sensitivity of 66%. The use of skin prick-test in the detection of causative allergens of human atopic dermatitis has proved to be a sensitive and specific tool frequently used by human allergists. Due to the number of similarities in canine and human atopic dermatitis, this could be a valuable tool that needs intensive research in veterinary medicine. The published research so far correlates to the results obtained in this investigation. However, future studies evaluating the concordance between in vitro specific IgE antibody assays and SPT must be carried out simultaneously to validate the test.